Risks in Prefabricated Buildings in China: Importance-Performance Analysis Approach - Zhong-Lei Wang (Sustainability, 2019)
Prefabrication has drawn wide attention in China during the last decade. However, the market share of prefabricated buildings in China remains comparatively low. The Importance-Performance Analysis approach is employed in this study to investigate the crucial risk factors associated with prefabricated buildings in China. A preliminary list of risks associated with prefabricated buildings in China was developed based on a critical literature review, which was consequently refined by the interview with related experts. A questionnaire survey was then conducted with selected industry professionals to solicit their expert opinions of critical risks associated with prefabricated buildings in China. Findings show that attention should be paid to the following risks: improper decomposition system, low level of factory management, incompetent quality assurance system, deviation in specification of prefabricated components, defects of component system, missing catalogue of building parts and components, poor adaptability of prefabricated building during the operational stage, and lack of actual cases to prove the environmental benefits of prefabricated buildings. This study also revealed the discrepancy between perceived critical risks and those risks with comparatively lower management performance. These findings offer useful inputs for the future development of prefabricated buildings in China and beyond.